Comparison of Botulinum Toxin Injection and Botulinum Toxin Injection with Glyceryl Trinitrate for Treatment of Chronic Anal Fissure - Kamran Liaqat, Rabail Rana, Saima Rasheed, Ayesha Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Anal fissure (AF) is an illness of anal canal and is characterized by cracks appearing in stratified squamous epithelium of distal anal canal. The tear, being present in the squamous part of the epithelium, causes considerable pain, fresh bleeding while defecation. The current study is planned to compare the Botulinum toxin Injection and botulinum toxin Injection with Glyceryl trinitate for the treatment of chronic anal fissure in terms of healing. Materials and Methods: Patients will be sent home after one hour with stool softener .while patients in group B will be will receive treatment with 0.2 ml (20 units) Botulinum toxin injection plus 1 gram 0.2% topical glyceryl trinitate cream 8 hourly with dose of 1 gram on middle fingers tip and apply it 1 cm2 in anal canal circumferentially. In both groups, patients will be assessed at follow up after 2 , 4 and 8 weeks post treatment. At follow up, patients will be examined for healing (yes or no) and any other side effect will be documented. Results: In Botulinum toxin injection group, 26(78.8%) had wound healing after 2 months and 30(90.9%) in Botulinum toxin injection with glyceryl trinitrate group with a p-value = 0.170. Conclusion: Botulinum toxin injection with glycerylyl trinitrate is a better technique for treatment of chronic anal fissure healing in comparison with Botulinum toxin injection alone. Keywords: Chronic Anal Fissure, Treatment, Botulinum Injection, Botilinum Injection with Glyceyl Trintrate, Comparison